The Use of Animated Video Media as Early Intervention in Teaching Writing Skills to Grade VII Students with Mild Intellectual Disabilities at SLB Putra Mandiri - Nurfadilah , Siti; Iskandar, Olga Madita; Ayu, Dyah Puspita (Universitas Negeri Surabaya, 2025)
In the current Generation Z era, the use of information technology-based media is still underutilized in special needs education, particularly for students with mild intellectual disabilities. Learning for students with such conditions will be more effective when supported by appropriate media that match their characteristics and needs. One potential solution is the use of animated digital video, which offers engaging visual and auditory stimuli to enhance students’ concentration. This study aims to describe how animated video can be used as an early intervention tool to support writing skills development in Grade VII students with mild intellectual disabilities at SLB Putra Mandiri. The research employed a qualitative descriptive method to observe and analyze the impact of using animated videos during writing lessons. The results showed that the animated video media improved students’ focus and engagement in the learning process. Students were more attentive and actively participated in writing tasks when animated videos were used. In conclusion, animated digital video media is proven to be an effective alternative learning tool that helps increase concentration and participation among students with mild intellectual disabilities during writing instruction.